Toxaphene Sounds Taps for Armyworms - Hercules Incorporated (1948 Hercules Advertisements, 1948)
Advertisement for Toxaphene, a toxicant manufactured and sold by the Hercules Powder Company for use in pesticides and insecticides. This advertisement appeared in the November and December 1948 issues of Agricultural Chemicals and Better Farming Methods. Formed in 1912 as part of an anti-trust settlement with DuPont, the Hercules Powder Company (later Hercules Inc.) initially specialized in the manufacture of explosives and smokeless powders and subsequently diversified its business to encompass a variety of industrial products, including pine and paper chemicals, synthetics, pigments, polymers, and cellulose.
Keywords: Toxaphene; Chemical industry; Hercules Incorporated; Insect pests--Control; Insect pests; Naval stores; Insecticides; Advertising, Industrial; Corporations